1999
DOI: 10.1093/jn/129.7.1412s
|View full text |Cite
|
Sign up to set email alerts
|

Inulin and Oligofructose: Safe Intakes and Legal Status

Abstract: Inulin and oligofructose are a significant part of the daily diet of most of the world's population. Daily intakes for the U.S. and Europe have been estimated at up to 10 g, specifically 1-4 g for the 97th percentile in the U.S. Because both inulin and oligofructose are macroingredients, it is difficult to apply classical toxicology tests. Although some high dose animal tests have been performed, none have revealed any toxic effects. The safety of inulin and oligofructose for use in foods was evaluated by many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
151
0
26

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(179 citation statements)
references
References 7 publications
2
151
0
26
Order By: Relevance
“…Fat is a major constituent that contributes to mouthfeel of dairy products. Coussement (1999) reported that when inulin used as a fat replacer, 0.25g of inulin was capable of replacing 1g of fat in foods. This fat replacing capacity of inulin could be a reason for enhanced mouth feel.…”
Section: Optimization Procedures and Verification Of Resultsmentioning
confidence: 99%
“…Fat is a major constituent that contributes to mouthfeel of dairy products. Coussement (1999) reported that when inulin used as a fat replacer, 0.25g of inulin was capable of replacing 1g of fat in foods. This fat replacing capacity of inulin could be a reason for enhanced mouth feel.…”
Section: Optimization Procedures and Verification Of Resultsmentioning
confidence: 99%
“…The actual intake and extent of use of these novel foods is, as yet, unknown. The doses required for these effects may cause adverse gastrointestinal symptoms such as bloating, borborygmi and flatulence in the majority of the population (Coussement, 1999;Bishop et al, 2009;Bonnema et al, 2010). The effects on faecal parameters demonstrate the colonic fermentation of these carbohydrates, but whether they have an effect on health outcomes is unclear; equally the biological relevance of the effect of non-digestible oligosaccharide and inulin supplementation on calcium fractional absorption in children is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This level of FOS intake was significant given the body weight of the rats was only somewhere between 90 -310 g. Taken together, the level of FOS intake by the rats in this study was very high relative to their body weight and should be adequate to show any enhancing effects, if FOS indeed improves iron status. As an aside, Moshfegh et al [20] estimated that the average intake of FOS was about 5 g/d in diets of American adults, and the acceptable intake of FOS could be as high as 30 g/d [21]. With an assumed body weight of 70 kg for an average American adult, an acceptable FOS intake would be equal to only 0.43 g/kg body weight.…”
Section: Weight Gain and Water Intakementioning
confidence: 99%